House prices, inflation and the mortgage market - Thom, Dr (Economic & Social Studies, 1983)
Abstract: This paper presents an analysis of house prices using quarterly Irish data over the period 1971-1980. Evidence is provided to support the hypotheses that real house prices are significantly influenced by the cost and availability of mortgage credit, the design of the mortgage instrument and the tax advantage of owner-occupation. Special attention is given to the role played by inflation which, when acting in concert with the tax and mortgage systems, affects the demand for housing services and real house prices.
Keywords: Economics; Sociology